Intimate partner violence among international college students in the US - Chaliawala, Kruti; Vidourek, Rebecca A.; King, Keith A. (Journal of International Students, 2025)
Intimate partner violence (IPV), although prevalent across the United States, is among the understudied topics in minority populations, such as international students on college campuses. The present study addresses the underexplored phenomenon of IPV among international college students, aiming to provide insights crucial for navigating relationships and educational pursuits. Utilizing data from the 2022 American College Health Association's National College Health Assessment (ACHA-NCHA) involving 13,242 international students, this research aims to demonstrate the prevalence of IPV within this understudied group. The results revealed an overall IPV prevalence of 13.7% within the last 12 months, with verbal abuse emerging as the most prevalent form. Univariate logistic regression indicated greater risks for graduate students (OR = 1.191, p < 0.001) and those without current relationships (OR = 1.000, p < 0.001). The final model confirmed that graduate student status and being single were significant predictors. This highlights how cultural adaptation, societal adjustment, and isolation increase vulnerability. This research highlights the pressing need for tailored prevention and support mechanisms and advocates targeted interventions, such as relationship education during college orientation, to promote equity, belonging, and global engagement among international students.